Manifestações sintomáticas na escrita e a clínica de linguagem - Fongaro, Anna Eliza Mattos (2009)
Based on written work of children undergoing phonological therapy, the discussion about the symptom aims to stand away from the language conception as object of knowledge. Such a distance is justified by considering that the language is not consisted of positive units which could be apprehended by the individual through his or her perception and cognition (ANDRADE, 2003) Functioning of language (SAUSSURE. 1916), former to individual and element of the triadic relation: individual language-the other, is responsible for the capture of the individual, placing him in the function of the language and promoting its division into the writing and reading instance. Implying this individual of Psychoanalysis demands to approach the subjectification issue also under the sexualization view (DE LEMOS, 1998, 1999, 2002). In the accomplished analysis, the materialness of writing is highlighted; segmentation and trace are fundamental elements. The hypo segmentations in the analyzed writing pieces are understood as speech elements that are present at writing (ABAURRE, 2002), they are the outcome of blending orality and writing under Language control (BORGES, 2006) a well as the forgotten possibilities of such function (CARVALHO,1995). In regard to the trace of the letters, it is underlined the homographic mistakes which brings the child s name latent under the manifest chains of writing (BOSCO, 1995). These mistakes are the outcome of the Language and demonstrate the child s alienation. The reflection about the symptom implied in considering the particular way of interweavement of an individual with/by the Language. The individual s unawareness of the reason for the occurrences of his writing and the impossibility of change point out the implication of the hypothesis of unconscious introduced by Freud (LIER DEVITTO, 2006). The operations of repression focus on the (visual and sound) image of the letters, indicated by Pommier (1996) allowed thinking about the symptom as an interweavement point of the subjectification with the language and by the language throughout the Oedipus complex passage